Changes of Intracellular Porphyrin, Reactive Oxygen Species, and Fatty Acids Profiles During Inactivation of Methicillin-Resistant Staphylococcus aureus by Antimicrobial Blue Light - Wu, Jiaxin; Chu, Zhaojuan; Ruan, Zheng; Wang, Xiaoyuan; Dai, Tianhong; Hu, Xiaoqing (Frontiers in Physiology, 2018)
Antimicrobial blue light (aBL) attracted increasing interest for antimicrobial properties. However, the underlying bactericidal mechanism needed to be verified. The hypothesis included the excitation of intracellular chromophores by aBL, subsequent generation of reactive oxygen species (ROS) and the resultant oxidization of various biomolecules. Thus, detecting the changes of intracellular biomolecules such as coproporphrin, singlet oxygen and ROS would help to uncover the physiological change and to confirm the underlying mechanism. Furthermore, it is of great significance to reveal novel targets of ROS, such as fatty acids. Therefore, these innovative works on methicillin-resistant Staphylococcus aureus (MRSA) were carried out in the current study. The results showed that aBL (5-80 J/cm2) exhibited bactericidal effect on MRSA, and almost no bacteria survived when 80 J cm2 had been delivered. Later, it was revealed that the concentration changes of intracellular molecules were associated with aBL irradiation. Firstly, coproporphyrin was decreased gradually, and meanwhile, ROS was increased rapidly. Especially, the emergence and increase of singlet oxygen were imaged, supporting the hypothesis. The severe oxidative stress resulted in the simultaneous increase of the lipid oxidative product MDA and intracellular K+ leakage, indicating the damage on lipids and permeability of cell membrane. More roughness on cell surface was also observed by atomic force microscope. All data above proved that cell membrane was target of ROS during aBL irradiation. Finally, to discover the target biomolecules, the fatty acids profiles at different illumination levels were compared by GC-MS. The relative content of three unsaturated fatty acids (C16:1, C20:1 and C20:4) were decreased and disappeared along with aBL irradiation, which likely played a key role in membrane injuries. The current study verified the changes of the intracellular biomolecules and revealed that lipids especially the unsaturated fatty acids in cell membrane lipids were target of ROS during aBL inactivation.